Estudo sazonal e circadiano do óleo essencial de Pectis brevipedunculata, desenvolvimento de microemulsão e avaliação do potencial sobre Rhipicephalus microplus e Haemonchus contortus - CAMARA, Marcos Bispo Pinheiro (2023)
Pectis brevipedunculata, belonging to the Astereceae family is a native species, popularly known as “tea de girl”, “rosemary do campo” and “lemongrass”, is widely found in dry and semi-arid ecosystems in the north and northeast regions, has a high production of essential oil with a high content of Citral, known for its antiparasitic effect. The essential oils (E.Os.) for being volatile can alter their constituents by climatic factors and pharmaceutical formulations can reduce chemical modifications and improve the biological effects of these E.Os. Therefore, the aim of this study was to evaluate the circadian and seasonal variation of P. brevipedunculata E.Os., as well as their acaricidal and anthelmintic effects and to develop formulations, especially nanoemulsions for incorporation of E.Os. Aerial parts were hydrodistilled and the chemical composition was determined by GC-MS. For the trials with Rhipicephalus microplus, larval immersion test and anthelmintic evaluation was performed on adults of Caenorhabditis elegans and later, on Haemonchus contortus, using the egg hatchability test. Toxicity tests were also performed on non- target organisms. For the development of the microemulsion, 20% of the E.O. was incorporated in a 7:3:1 ratio of oil: surfactant:water. The chemical composition result identified the presence of 30 constituents, the majorities being citral, α-pinene, and D-limonene, with a predominance of oxygenated monoterpenes. For the seasonal period, the highest yield was observed in April (2.08%) and August (2.05%). For the circadian, the highest yields (2.0% and 1.2%) were at 18hs, for both dry and rainy seasons, respectively. Regarding the tick activity, the E.Os. from April (LC50 1.17 mg/mL), March (LC50 1.28 mg/mL) and October (LC50 1.27 mg/mL) obtained in the seasonal analysis were the most efficient. In the circadian rhythm, the rainy and dry seasons at 6 p.m. and 12 a.m. exhibited the lowest LCs50. The E.O. also proved to be selective for non-target organisms. For C. elegans the E.Os. of P. brevipedunculata exhibited an anthelmintic effect against adults of the nematode, showing inhibitory concentrations lower than 0.8 mg/mL for seasonal cycle and 1.85 mg/mL for circadian rhythm. For H. contortus, all E.Os. tested on H. contortus eggs showed strong anthelmintic effects, exhibiting ICs50 below 0.5 mg/mL. The percentage of tick activity of the microemulsion against R. microplus larvae showed 100% efficiency when compared to the non-formulated E.O. (22% inhibition). It is concluded that E.O. from P. brevipedunculata contain bioactive compounds with great potential to control parasites and the biotechnological process of microemulsion systems may be a viable alternative to turn the bioproduct into a stable formulation and more efficient in controlling these parasites.